(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
To study the level of physical readiness of girls aged 15-17, who go in for Thai boxing, to develop and evaluate the effectiveness of individual pedagogical programs for the correction of lagging physical qualities.